2015
DOI: 10.1002/ijop.12225
|View full text |Cite
|
Sign up to set email alerts
|

The importance of feeling sexually attractive: Can it predict an individual's experience of their sexuality and sexual relationships across gender and sexual orientation?

Abstract: Limited research exists on the implications of feeling sexually attractive for various aspects of sexuality and sexual relationships. This article examined associations between self-perceived sexual attractiveness and sexual esteem, sexual satisfaction and amount of sexual experience, among both men and women who identified as heterosexual (n = 1017), gay or lesbian (n = 1225) or bisexual (n = 651). Results of the study demonstrated that positive self-perceptions of sexual attractiveness predicted greater sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 33 publications
1
3
0
4
Order By: Relevance
“…As suspected, perceived rejection and self-perceived sexual attractiveness were highly significant across all six models, where higher scores on perceived rejection were associated with worse psychological wellbeing, and higher scores on self-perceived sexual attractiveness were associated with better psychological wellbeing. These results are consistent with the literature examining the association between selfperceived sexual attractiveness and self-perceived rejection on psychological health outcomes (Amos & McCabe, 2017;Bale & Archer, 2013;Downey & Feldman, 1996;Nolan et al, 2003). Moreover, these two variables had the largest effect sizes of any variable across all six models, suggesting that they are two essential factors to account for in the context of RSD.…”
Section: Control Variables and Psychological Wellbeingsupporting
confidence: 89%
See 1 more Smart Citation
“…As suspected, perceived rejection and self-perceived sexual attractiveness were highly significant across all six models, where higher scores on perceived rejection were associated with worse psychological wellbeing, and higher scores on self-perceived sexual attractiveness were associated with better psychological wellbeing. These results are consistent with the literature examining the association between selfperceived sexual attractiveness and self-perceived rejection on psychological health outcomes (Amos & McCabe, 2017;Bale & Archer, 2013;Downey & Feldman, 1996;Nolan et al, 2003). Moreover, these two variables had the largest effect sizes of any variable across all six models, suggesting that they are two essential factors to account for in the context of RSD.…”
Section: Control Variables and Psychological Wellbeingsupporting
confidence: 89%
“…SPSA, researchers note, is distinct from general perceptions about one's physical attractiveness and is therefore a particularly relevant construct when negotiating the possibility of a sexual encounter (Wade, 2000). Among the general population, researchers have reported that positive perceptions of one's own sexual attractiveness are associated with indicators of psychological wellbeing, such as self-esteem (Amos & McCabe, 2017;Bale & Archer, 2013). Among sexual minority populations, SPSA specifically has been largely underinvestigated, but body image and other appearance-related concerns are widely reported and associated with greater depressive symptoms relative to heterosexual populations (Dahlenburg et al, 2020;Ehlinger & Blashill, 2016).…”
Section: Contributing Factors To Psychological Health In Online Partner Seekingmentioning
confidence: 99%
“…Presentar compulsión sexual (Starks, Grov y Parsons, 2013), haber sido víctima de abuso sexual infantil (Crump y Byers, 2017;Weingourt, 1998), el abuso de alcohol (Dolezal, Remien, Wagner, Carballo-Diéguez y Hung, 2015), mayor edad (Biss y Horne, 2005;De Ryck et al, 2012), tener relaciones sexuales sin el consentimiento propio (De Ryck et al, 2012), la preocupación por adquirir una infección de transmisión sexual (De Ryck et al, 2012), tomar fármacos que reducen la libido (De Ryck et al, 2012;Motofei, Rowland, Popa, Kreienkamp y Paunica, 2011) y mayor percepción de malestar (Burri et al, 2012), presentar un estilo de apego de tipo ansioso o evitativo (Mark, Patrick y Murray, 2017) son variables asociadas con niveles bajos de satisfacción sexual. Por otra parte, mantener ilusiones sexuales positivas, es decir, tener la percepción de que con la pareja se tienen similitudes y complementariedad (De Jong y Reis, 2015), tener una buena autopercepción del atractivo sexual (Amos y McCabe, 2015) y motivos para tener relaciones sexuales con el fin de mejorar la intimidad con la pareja (Sánchez, Moss-Racusin, Phelan y Crocker, 2011) son variables personales relacionadas con mayor satisfacción sexual.…”
Section: •Instrumentos Empleadosunclassified
“…Variables asociados a la satisfacción sexual Tipo de variable Amos y McCabe (2015) Población general: hombres heterosexuales (n = 549), hombres homosexuales (n = 979) y hombres bisexuales (n = 273). Mujeres heterosexuales (n = 468), mujeres homosexuales (n = 246) y mujeres bisexuales (n = 378) Población general: hombres heterosexuales (n = 2.968) y hombres homosexuales (n = 285)…”
Section: Autoresunclassified
“…En contra de lo observado en estudios anteriores (Amos & McCabe, 2017;Björkenstam et al, 2020;Ritter et al, 2018), donde las personas heterosexuales eran las que mostraban mayor satisfacción sexual, en el presente trabajo son las mujeres plurisexuales y las heterosexuales las que más satisfechas están con su vida sexual, y los hombres plurisexuales, por el contrario, los que menos satisfacción sexual muestran.…”
Section: Hipótesisunclassified